Determination of instantaneous values of power components in an electronic voltage and current transformer - Tankevych, Serhiy; Chopyk, Vasyl (Publishing House of Lviv Polytechnic National University, 2012)
The method of determining instantaneous power components is based on the application of the p-q-r theory. The implementation of this method allows analyzing the components of instantaneous power and using the data for the purposes of various secondary systems. Подано метод визначення складових миттєвої потужності, що ґрунтується на застосуванні p-q-r теорії. Реалізація цього методу в цифровому трансформаторі струму та напруги дозволяє проаналізувати складові миттєвої потужності і використовувати отриману інформацію для потреб різного роду вторинних систем.
Визначення миттєвих значень складових потужності в електронному трансформаторі струму та напруги
Keywords: electronic transformer; power; instantaneous power theory; control system